Svaveldirektiven och de svenska raffinaderierna – den framtida situationen - Svensson, Jenny; Skoglund, Karolina (My University, 2015)
Crude oil contains large amounts of emissions, such as sulphur and aromatics and it is imported into refineries and the products that the market demands are produced, such as different types of marine fuels. The maritime industry has a significant amount of sulphur emissions in the world, but it is not easy to replace it with another transportation. Lately, sulphur emissions from the maritime industry have come under scrutiny and new regulations has come into effect. SECA 2015 is a sensitive area consisting of North Sea, Baltic Sea and English Channel and regulates the sulphur content in fuels to maximum 0,1 percent in marine fuels. SECA 2015 is the start of an era with new regulations and directives to be implemented in the future. Year 2020 or 2025 there will be a global lowering and the directive will regulate the maximum sulphur content in fuels to 0,5 percent in marine fuels. This thesis is a case study on how well prepared the Swedish refineries are for future sulphur regulations and what strategies they have to avoid losing market shares to competing refineries in Europe and in the world. The thesis is based on literature from different sources and three semi-structured interviews with the refineries Preem AB and St1 and also with the customized consulting company Maritime-Insight. The result indicates that the two refineries in Sweden were very well prepared for SECA 2015 and that the price- and market impact was manageable. However, it will require a well-formulated strategy and a long-term plan for the future to meet the global directives. Preem and St1 believe that the industry needs to be more streamlined to be able to compete against the stronger competition in the future.
Keywords: Transport; Hållbar utveckling; Transportteknik och logistik; Transport; Sustainable Development; Transport Systems and Logistics